Pengaruh inovasi produk olahan nanas terhadap keunggulan bersaing berkelanjutan (studi pada Koperasi Kelompok Tani Tunas Makmur di Desa Kampung Jawa Kabupaten Bengkalis) - Halimatussadiah Halimatussadiah; Annisa Mardatillah (SYNERGY: Jurnal Bisnis dan Manajemen, 2021)
Research conducted by the author aims to see the effect of innovation of processed pineapple products on sustainable competitive advantage (a study on the cooperative of a prosperous bud farmer group in the village of Kampung Jawa, Bengkalis Regency). This Research also aims to determine the dimensions of product innovation that have the most influence on sustainable competitive advantage. Sampling using saturated sampling method or census. The data in this research were obtained through a questionnaire, and the data analysis used was simple regression analysis with the SPSS v.22 application. The results of data analysis show that the innovation of processed products partially affects sustainable competitive advantage (a study on the cooperative of a prosperous bud farmer group in the village of Kampung Jawa, Bengkalis Regency).